Resistant machanisms, dynamic properties and inhibitor development of neuraminidase in influenza virus : molecular dynamics simulations studies - Han, Nanyu (2014)
Since the beginning of the last century, several pandemics with high morbidity and mortality caused by influenza viruses have occurred, and posed great threat to human life. Although vaccines and antiviral drugs have been developed to treat the upcoming influenza viruses, the accumulating mutant viral strains weaken the power of antiviral strategies. In order to efficiently treat this infectious disease, it is critical to understand the molecular basis of the drug resistance mechanisms of influenza viruses. The aim of this work is to investigate drug resistant mechanisms at the molecular level, to explore structural plasticity of the target protein and to provide promising ligands that can effectively bind the influenza target protein through computational methodologies. Recently, H1N1 strains of influenza A carrying a mutation of Q136K in neuraminidase (NA) were reported. This new strain showed a strong zanamivir (ZMR, an antiviral NA inhibitor) neutralization effect. In the first study, normal molecular dynamics (MD) simulations and metadynamics simulations were employed to explore the mechanism of ZMR resistance. Hydrogen-bond network analysis showed weakened interaction between the ZMR drug and E276/D151 on account of the electrostatic interaction between K136 and D151. Metadynamics simulations showed that the free energy landscape in the mutant is different from that in the wild type (WT) NA, suggesting weaker binding. This study indicates that the deformation of the 150-loop combined with the induced altered hydrogen-bond network is the reason for development of ZMR resistance. In addition, Hamiltonian replica exchange molecular dynamics (HREMD) simulations were performed to explore the plasticity of the 150-loop, which had been found to be crucial in maintaining the stability of the ZMR. The free energy landscape of the 150-loop was extensively sampled, and the most dynamical motif was identified. This enhanced sampling simulation together with the discovery of a drug resistance mechanism provides invaluable information in structural-based drug discovery against influenza viruses. Based on these two findings, the 150-loop seems to be a hotspot for influenza drug development. Thus, a combined virtual screening and MD simulations method was applied to design ligands that specifically target the 150-cavity based on the structure template of ZMR. Finally, one ligand was found to stably interact with NA and lock the 150-loop in an open configuration. After comparing to both positive and negative controls, this newly designed ligand was shown to possess the highest binding affinity. More generally, the key interactions between NA and inhibitors were also identified which provides references for novel inhibitors design. Our study provides a possible route in designing new NA inhibitors for combating the spread of influenza virus.